Analisis Faktor-Faktor yang Mempengaruhi Impor Beras di Indonesia - Basia, Lusmino; S, Suripto; Wiliyanto, Eko (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Based on data from the Food and Agriculture Organization (FAO), Indonesia's rice production since the last three years has continued to increase, making Indonesia the third largest rice producing country in the world. This study aims to analyze the factors affecting rice imports in Indonesia with selected economic variables: foreign exchange reserves, rice consumption, rice production, GDP per capita, and inflation. This study used quantitative methods with secondary data. Data used in this study from 1980 to 2019. Data sources are obtained through data from the Central Statistics Agency (BPS), Bank Indonesia (BI), International Rice Research Institute (IRRI), World Bank, Ministry of Agriculture. The analysis method uses multiple linear regression analysis. The results of this study show that the variable of foreign exchange reserves has a significant positive effect on rice imports. The variables of rice production and GDP per capita have a significant negative effect on rice imports in Indonesia, while the variables of rice consumption and inflation do not affect rice imports in Indonesia.